Ensayo comparativo de 24 genotipos de Sorgo Granífero (Sorghum Vulgare) en Morales - Bajo Mayo - Abanto López, Néstor Porfirio (1993)
In order to determine the most promising genotypes for our environment based on yield components and desirable agronomic traits; A comparative test of 24 genotypes of grain sorghum including a commercial hybrid that acted as a witness was conducted. The experiment was carried out on the moral grounds of the National University of San Martin, located in the district of Morales -Low Mayo, San Martin Region; in a entysol ground texture frank, deep, well-drained sand; low content of organic matter, phosphorus and potassium and 6.0 ph The experimental setup used was randomized complete block with 4 replications; with 4 rows for each experimental unit, spaced 0.50m. and planted a continuous stream; adopting a density equivalent to 140,000 plants / ha. After desashije Fertilization was carried out 100-60-60 formula being used, having been split into 3 parts nitrogen. Earthworm attacks occurred, which caused failures bereave them of children; also there was prevalence of armyworm and sugarcane controlled effectively the same as reaching a 25% infection. No consideration diseases were presented. The results of interest were: The lower coefficients of variability in relation to other features, accounted for: plant height, stem diameter, number of panicles and grain weight field. M-90362 genotype showed the highest yield potential with 5,163_18kg / ha. Grain, without differ significantly genotype M-82639-1 which reached 4,618.05kg / ha. And the SAR-24 obtained 4.44.9kg / ha .; but showing significant superiority to others, including the witness.Finally, it is recommended to set benchmarks with the 8 first in order of merit genotypes